IIIe Biennale Internationale de la Gravure Cracovie 1970. - Dzieduszyki, Antoni; Krakowski, Piotr; Wejman, Mieczyslaw; III Miedzynarodowe Biennale Grafiki Kraków, 1970 (Krakow, : Ministerstwi Kultury i Sztuki, 1970)
Afro ; Agger, Poul ; Aleksiun, Jan Jaromir ; Alicea, Jose ; Almlöf, Bertil ; Alsheik, Yahia ; Alun, Leach-Jones ; Anderle, Jiri ; Andersen, Knud ; Andronescu, Ana-Maria ; Antinori, Giorgio ; Apolonio, Marina ; Araki, Tetsuo ; Arlin, Richard ; Arnaiz, Doroteo ; Arpad, Bognar ; Arrak, Jüri ; Assadour ; AY-O ; Backen, E. ; Baias-Lucaci, Ethel ; Bak, Imre ; Baldessin, George ; Balkanski, Pentcho ; Banaszewski, Roman ; Baranyay, Andras ; Bates, Pat Martin ; Bednarova, Eva ; Behring, Edith ; Benjamin, Anthony ; Benon, Jean-Pierre ; Bertemes, Roger ; Bessoudo Courvoisier, Ruth ; Bettiol, Zoravia ; Beutlich, Tadeusz ; Biasi, Alberto ; Bischof, Peter ; Bitzan, Ion ; Blume-Bensler, Christel ; Boberg, Jörgen ; Böckman, Bengt ; van den Bogaert, Ilse ; Boguslawska, Joanna ; de Bolle, Francis ; Boratynski, Antoni ; Borcic, Bogdan ; Borysowski, Stanislaw ; Boukhatem, Fares ; Boyaner, Mel ; Boza, Juan ; Brachel-Golen, Ewa ; Braun, Theo ; Bravo, Alfredo Sosa ; Breiter, Herbert ; Breivik, Anne ; Bresciano, Miguel ; Brillant, Gilberte ; Broniek, Zofia ; Brunovsky, Albin ; Bucci, Domingo ; Buckley, Sue ; Bunsch, Franciszek ; Burkiewicz, Franciszek ; Camnitzer, Luis ; Capozzoli, Glauco ; Carballo, Aida ; Carcan, René Marcel ; Carlier, Yolaine ; Carmi, Eugenio ; Casanova, Teresa ; Castro, Lourdes ; Caubios, Jean-Pierre ; Chaves Barcellos, Vera ; Chirnoaga, Marcel ; Chirot, Holley ; Chrea, Ing ; Chrostowska, Halina ; Chutkowska-Kaminska, Krystyna ; Claesson, Rune ; Cok, Zlatana ; Connal, Betty Peebles ; Contino, Jose ; Copello, Francisco ; Cornuz, Christiane ; Cox, Lizzie ; Crapp, Shirley ; Cruz, Eduardo Fagundes ; Cugat, Della ; Cyorovic, Slavoljub-Slavko ; Dacos ; Dag, Arnljot Rodsand ; Damer, Jack ; Damski, Stefan ; Dawski, Stanislaw ; Debenjak, Riko ; Dembo, Aleksandr ; etc.
biografie
IIIe Biennale Internationale de la Gravure Cracovie, 1970
Frans & Pools
boek